Protective Effect of Urtica dioica Seeds’ Extract in Experimental Chronic Aflatoxicosis in Broiler Chickens - Ayna, Erhan; Huyut, Zübeyir; Keleş, Omer Faruk; Yener , Zabit; Bal, Ramazan (International Journal of Poultry Science, 2021)
Background and Objective: Aflatoxins can lead to Aflatoxicosis in animals and humans. The aim of this study was to investigate hepatoprotective and antioxidant effect of Urtica dioica seeds’ extract (UDSE) on chronic aflatoxicosis in broiler chickens, which were evaluated by histopathologically liver degeneration and activities/levels of the oxidative stress and antioxidant parameters. Materials and Methods: Thirty-two broiler chickens were randomly divided into four experimental groups: control group served as a negative control and were fed with a normal diet; AFB1 group received aflatoxin B1 (AFB1) (1 mg kg–1 diet) for 42 days; UDSE group received UDSE (30 mL kg–1 diet) for 42 days and AFB1+UDSE group received AFB1 (1 mg kg–1 diet) as well as UDS extract (30 mL kg–1 diet) for 42 days. Results: In the AFB1 group, activities of SOD, GSH-Px and CAT and the levels of TAS and BcL-2 in liver and serum were significantly lower than that of the control group (p